2007
DOI: 10.1111/j.1467-629x.2007.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

On the intertemporal value relevance of conventional financial accounting in Australia

Abstract: This paper examines whether the relevance of conventional (earnings focused) accounting information for valuation has declined in Australia over a recent period of 28 years. Motivation is provided by the anecdotal concerns of financial analysts, accounting regulators, and a cluster of US centric academic research papers that conclude that the relevance of financial accounting (and earnings in particular) has declined over time. After controlling for nonlinearities and stock price inefficiencies, we find that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 27 publications
3
48
1
2
Order By: Relevance
“…In this nexus, accounting information is crucial, as the extant literature has demonstrated that accounting information is related to value, and by extension, relevance (Ball & Brown, 1968;Beaver, 1968;Lee, 1989;Brimble & Hodgson, 2007). Biesland (2008) defines value relevance as the ability of financial statement information to capture and summarize information that determines firm value.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…In this nexus, accounting information is crucial, as the extant literature has demonstrated that accounting information is related to value, and by extension, relevance (Ball & Brown, 1968;Beaver, 1968;Lee, 1989;Brimble & Hodgson, 2007). Biesland (2008) defines value relevance as the ability of financial statement information to capture and summarize information that determines firm value.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%
“…The study conducted by Ball and Brown (1968) is one of the earliest comprehensive study investigating the association between unexpected earning and abnormal stock returns. Thereafter, a significant body of research has been conducted in the context of different markets (e.g., Amir, Harris, &Venuti, 1993;Collins, Maydew, & Weiss, 1997;Holthausena & Watts, 2001;Brimble & Hodgson, 2007;Soderstrom & Sun, 2007). Holthausena and Watts (2001) classified the studies relating to value relevance into three sub-classes: 'relative association studies', 'incremental association studies', and 'marginal information content studies'.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model provides a valuation 3 International evidence of the debate of comprehensive income reporting in countries such as UK and New Zealand can be found in O'Hanlon and Pope (1999), Cahan et al (2000), Brimble and Hodgson (2007), and Lin (2006). framework that includes many different parameter inputs which generate a wide range of estimates that can be presented statistically by a distribution with a mean and variance. The user of the model can easily examine the implication of alternative underlying firm-level and economy-wide environment changes on the equity share prices.…”
Section: Warren and Shelton Model (1971)mentioning
confidence: 99%